Binding of per- and polyfluoroalkyl substances with liver and serum proteins in rats: implications for physiologically based pharmacokinetic modelling - Xiarui Fan; Xiaomin Li; Tong Li; Bing Shao; Shan Niu; Wenhong Fan; Qi Wang; Lv Zhong; Xiangrui Wang; Ziwei Wang; Fujun Ma; Guomao Zheng; et al. (Environment International)
Understanding the binding between per- and polyfluoroalkyl substances (PFAS) and proteins is essential for elucidating their toxicokinetics and tissue distribution. Here, we quantified the binding affinities of 14 PFAS to rat liver fatty acid-binding protein (rL-FABP) and rat serum albumin (RSA). Results showed that PFAS exhibit strong binding affinities (Ka) to the rL-FABP (103 ∼ 105 M−1), particularly among medium- to long-chain perfluorinated carboxylic acids (PFCAs). The binding affinity of PFAS to RSA ranged from approximately 104 to 105 M−1, with 1 to 4 binding sites. Molecular docking results supported that PFAS binding to proteins is an exothermic process driven by van der Waals forces, hydrogen bonding, and electrostatic interactions. Additionally, long-chain PFCAs were shown to adopt a “U”-shaped conformation within the ligand-binding cavities of rL-FABP and RSA. The newly developed physiologically based pharmacokinetic model using measured binding data demonstrates a substantial improvement in the goodness of fit to experimental observations, reducing the prediction error by 20 %∼216 %. Finally, we found that the PFAS liver-blood partition could be mainly explained by the binding affinity ratios of PFAS to liver and blood proteins, which could be further extrapolated from rats to humans, providing useful insights to understand the tissue distribution of PFAS.